MANAJEMEN PEMBINAAN ATLET SHORIJNI KEMPO DI DOJO UNIVERSITAS KRISTEN ARTHA WACANA KUPANG - Umbu Talu OLi (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2020)
The purpose of this study was to find out about Planning, Organizing Movement, Supervision in the Dojo of Artha Wacana Christian University, Kupang. The subject of this research is to see and know about the Management of Athlete Development Shorinji Kempo at the Dojo of Artha Wacana Christian University, Kupang. where the research was carried out in the Dojo of the Artha Wacana Christian University, Kupang. The method used in this research is descriptive with a qualitative approach. The instruments used were observation guidelines and interviews with administrators, coaches and athletes. In this study, triangulation techniques are used, namely data validity checking techniques that utilize something other than the data for checking purposes or as a comparison of the data. It can be concluded that, the Artha Wacana Christian University Dojo, Kupang, is one of the training venues, the process of coaching and recruiting kenshi to become outstanding athletes. Based on the results of research and findings in the field by researchers, through observations and interviews that were considered prominent was the recruitment and coaching process of kenshi at the Dojo which was so good and got enthusiasm when practicing from kenshi and trainers, based on document studies, researchers did not find any training program designed by or coach.